Mercosur's regional health agenda: architecture and themes - Luisa Guimaraes Queiroz; Ligia Giovanella
This article describes the shaping of institutional health spaces in the Mercosur, with analysis of themes and results and considerations on the construction of the regional agenda and on the effects of regional economic integration processes on health policies and systems. We discuss the organization, operation, focus topics, and results achieved in specific health forums (Meeting of Ministers of Health and Sub-Working Group 11), seeking to analyze the architecture and issues addressed by the regional agenda and drawing parallels with the European experience. The aim of this reflection is to identify how the work done by Mercosur structures contributes to building a regional agenda, with the expectation that the integration can contribute to reducing inequalities in access to health care in the region.